2018
DOI: 10.1093/aobpla/ply077
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis uncovers the genetic basis of general combining ability of 11 yield-related traits in parents of hybrid rice

Abstract: Association analysis between constructed single nucleotide polymorphism linkage disequilibrium blocks (SNPLDBs) and general combining ability (GCA) effects is a novel approach to uncover the genetic basis of GCA within the sequence genomes of parents of hybrid rice. Here, we calculated the GCA effect values of 33 parents of hybrid rice and sequenced them to identify genome-wide single nucleotide polymorphisms (SNPs). In total, 64.6 % of the uniquely mapped paired-end short reads revealed a final total of 291 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…qRN3-1 and qRN6, two pleiotropic loci, were associated with the GCA effects of RN, KW, and HKW rather than these per se performances for the traits. The two loci were not been identified in previous study (Qi et al, 2013), the specificities in additive effects might be caused by diverse testers (Qu et al, 2012), the identified loci occurred due to the presence of potential GCA coverage in the potential genomic regions (Zaid et al, 2019). Furthermore, qKT1-2 and qHKW5-1 were two stable loci for GCA effects of KT and HKW respectively, but no significant loci were detected for corresponding per se performances for the traits in multiple environments.…”
Section: Potential Utilization Of Main Qtl For Gca Effects In Maize Hmentioning
confidence: 69%
“…qRN3-1 and qRN6, two pleiotropic loci, were associated with the GCA effects of RN, KW, and HKW rather than these per se performances for the traits. The two loci were not been identified in previous study (Qi et al, 2013), the specificities in additive effects might be caused by diverse testers (Qu et al, 2012), the identified loci occurred due to the presence of potential GCA coverage in the potential genomic regions (Zaid et al, 2019). Furthermore, qKT1-2 and qHKW5-1 were two stable loci for GCA effects of KT and HKW respectively, but no significant loci were detected for corresponding per se performances for the traits in multiple environments.…”
Section: Potential Utilization Of Main Qtl For Gca Effects In Maize Hmentioning
confidence: 69%
“…GCA analysis seeks to facilitate breeding through effective and efficient selection of inbred lines for a cross based on additive and additive × additive gene effects. Moreover, GCA analysis maximize additive gene effect that increases the selection efficiency of breeders in selecting elite inbred parents with better performance (Ullah Zaid et al, 2019)we calculated the GCA effect values of 33 parents of hybrid rice and sequenced them to identify genome-wide single nucleotide polymorphisms (SNPs. The RILs from the cross between the maintainer line Zhenshan97B and the restorer line Minghui63 (both parents of the elite hybrid Shanyou63, the classical hybrid of three-line system) was used to create the subsequent immortalized F 2 population, which enabled the comprehensive evaluations of the genetic contributions of dominance, over-dominance and epistatic effects across the whole rice genome (Liu et al, 2020).…”
Section: Specific Combining Ability (Sca) Ef-fectsmentioning
confidence: 99%